Fungal recovery and characterization from Hindu Kush mountain range, Tirich Mir glacier, and their potential for biotechnological applications. (9th March 2020) - Rafiq, Muhammad; Nadeem, Shaukat; Hassan, Noor; Hayat, Muhammad; Sajjad, Wasim; Zada, Sahib; Sajjad, Wasim; Hasan, Fariha
Abstract: The Hindu Kush mountains spread over Northern areas of Pakistan having hundreds of glaciers representing a unique ecosystem driven by the specific geochemistry and climate. The current study measured the distribution of culturable fungi in Tirich Mir glacier, Hindu Kush range, and the potential of these isolates to show antimicrobial activity and produce biotechnologically important enzymes. Samples of glacial ice, sediments, and meltwater were collected from Tirich Mir glacier, and 46 fungal strains were isolated and characterized for identity and biotechnological applications. The findings revealed Penicillium (10) as the most common genus, followed by Alternaria (9), Cladosporium (7), Coprinopsis, two isolates each belonging to genus Phoma, Ulocladium, Epicoccum, Onygenales, and Didymella, and one isolate of genus Davidiella, Aspergillus, Geomyces, Dothideomycetes, Pseudogymnoascus, Irpex, Scopulariopsis, Ascochyta, Tomicus, and Davidiellaceae. Davidiella tassiana HTF9 showed growth in the presence of 18% NaCl and pH 2, 3, 5, 7, 9, and 11. The isolates Ulocladium sp. and Onygenales sp. inhibited the growth of test fungi, Gram‐negative and positive bacteria. Fungal strains were capable of producing cold‐active enzymes, including cellulase, lipase, amylase, and deoxyribonuclease. The isolate Penicillium chrysogenum HTF24 was an efficient producer of amylase, deoxyribonuclease, and cellulase. The fungi of high‐altitude glaciers are potent candidates for biotechnological applications; however, studies using more sensitive techniques are needed for further exploration.